The effect of cataloging anxiety on the job preference of library and information science students - Padoginog, Liezle E.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
This study focused to determine whether the students of the School of Library and Information Studies taking cataloging subjects during the second semester of school year 2007-2008 are cataloging anxious and whether the students would consider cataloging for their future jobs. The study determined the predictors of work preference, namely: confidence, students' teacher perception, and subject usefulness. Among the respondents of this research were the students taking LIS 61 (Cataloging and Classification I) and LIS 62 (Cataloging and Classification II). The respondents were asked to catalog and answer a survey.
There were four statistical analyses used to analyze the results of the survey, namely: chi-square, frequency, correlation and regression. Chi-square showed that there is no relationship among the experimental grouping and the attitudinal ratings. Frequency showed that 20 respondents preferred cataloging as work, 16 were still unsure of their work preference and the remaining 5 respondents expressed their aversion for cataloging as work. The correlation between work preference and subject usefulness is the only factor that proved a significant relationship as a predictor in 0.05 and 0.01 alpha. This implies that students with higher rating in the items regarding subject usefulness were more probable to consider cataloging as their future job preference. The results of correlation, as a whole or according to the experimental groups showed no relationship between the variables confidence, students' teacher perception, subject usefulness, and their work preference. Regression showed that the variables cannot be used as reliable predictors for work preference. If the results had been positive significant relationships, assuming that a student gave high ratings in confidence, subject usefulness, and student's teacher perception, one can logically assume that the student prefers to work as a cataloger.
The study revealed that students of LIS 61 and 62 last second semester during the academic year 2007-2008 were not "cataloging anxious" based on the average scores in the survey-experiment. With respect to the experimental groups, there were no significant differences in the anxiety scores. The study showed that the causal relationships among the factors: confidence, subject usefulness, and students' teacher perception, and the dependent variable, work preference were insignificant. The researcher recommends that future studies increase the number of respondents and widen the rating scale used in attitudinal ratings from the Likert 1-5 to 1-10.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines. School of Library and Information Studies -- College students; Cataloging; Anxiety